Avaliação teórica - experimental de um sistema de refrigeração por absorção acoplado a uma unidade de microcogeração. - Queiroz, Daniel Ferreira (2013)
The present study presents a theoretical and experimental analysis of a cogeneration plant composed of one absorption chiller that uses technology NH3/H2O, a heat exchanger and a generator by natural gas. A thermodynamic model was developed in computational platform EES (Engineering Equation Solver) and it's based on ideal processes, information supplied by the engine manufacturer and the absorption chiller, as well as experimental results and literature. This work also aims to expose constructive characteristics, experimental methodology adopted, problems identified, interventions and the solutions adopted in the resolution of problems occurring.